A facile electrochemical sensor based on titanium oxide (TiO2)/reduced graphene oxide (RGO) nano composite modified carbon paste electrode for sensitive detection of epinephrine (EP) from ternary mixture. (2021) - Joseph, Teena; Thomas, Nygil
Abstract: Titanium Oxide/Reduced Graphene Oxide (TiO2 /RGO) nano composite was prepared using hydrothermal method using titanium butoxide and Graphite oxide (GO). GO was synthesised by following modified Hummers method. The prepared materials were characterised by Powder X-ray Diffraction (PXRD), Fourier Transform Infrared Spectroscopy (FT-IR), Thermogravimetry combined with Differential Scanning Calorimetry (TG-DSC). An electrochemical sensor based on TiO2 /RGO nano composite was constructed for sensitive and selective detection of epinephrine (EP). Due to greater surface area, TiO2 /RGO nano composite modified carbon paste electrode (TiO2 /RGO-MCPE) shows enhanced electrocatalytic activity towards the oxidation of EP by increasing anodic current. The differential pulse voltammetric (DPV) technique shows that EP could be detected independently and simultaneously from a mixture of ascorbic acid (AA) and uric acid (UA) using TiO2 /RGO-MCPE. The developed sensor shows good reproducibility, stability and two linear dynamic ranges 0.005–0.1 mM and 0.1–2 mM respectively.